Development of Surface Drifting Buoys for Fiducial Reference Measurements of Sea-Surface Temperature - Le Menn, Marc; Poli, Paul; David, Arnaud; Sagot, Jérôme; Lucas, Marc; O'Carroll, Anne; Belbeoch, Mathieu; Herklotz, Kai (Frontiers in Marine Science, 2019)
This paper presents the conception and the metrological characterization of a new surface drifting buoy, designed to comply with the requirements of satellite sea-surface temperature measurement validation and to link, per comparison, these measurements to the SI. The reliability of this comparison is ensured by a High Resolution Sea-Surface Temperature (HRSST) sensor associated with a pressure sensor in a module called MoSens. This module can be calibrated in a laboratory to ensure traceability to the SI with an expanded uncertainty inferior to 0.01 °C. Once integrated in a number of buoys, the resulting network will contribute to create a fiducial reference measurement network. The pressure sensor can be used to estimate the sea-state, which is important to consider in order to understand the comparison with satellite data. Two buoy prototypes have been tested at sea during several weeks and compared in situ to reference thermometers, demonstrating their reliability and the accuracy of temperature measurements.